STATUS EKOSISTEM PESISIR BAGI PERENCANAAN TATA RUANG WILAYAH PESISIR DI KAWASAN TELUK AMBON - Asyiawati, YULIA; YULIANDA, FREDINAN; DAHURI, ROKHMIN; R.P. SITORUS, SANTUN; SUSILO, SETYO BUDI (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2010)
This study aims : (1) to analyze the status of coastal ecosystems, (2) to analyze factors that affect the quality of coastal ecosystems, and (3) to prepare the direction on spatial planning in coastal areas of Ambon Bay Area.The analytical method used in this study is the analysis of ecosystem status, principal components analysis, analysis of Geographic Information Systems (GIS) and analysis of dynamic systems.The results showed that the condition of ecosystem status damaged in 2008, whereby, the status of mangrove ecosystems is moderate with a density of 1100 trees/ha, the status of seagrass ecosystems damaged by percentage cover of 38,76%, and the status of coral reef ecosystems are damaged by the percentage of live coral is 42,27%. Ecosystem conditions in Ambon Bay Area is affected by land use on land, namely forest area and population.Refferral of land use planning in Ambon Bay Areas wich recommended in this study for a period of 20 years of protected areas and cultivated areas. Protected areas is aimed at 9.480,70 ha or 41,21% of land area, while the allocation of space for the cultivation area is 10.416,30 ha (58,79% of land area). To reduce the pollutant into the waters, planned buffer zones (coastal and riverine border for 11,69% of land area), which serves to absorb pollutants and protect the inland waters of the tidal influence, while still controlling the waste coming into waterBy using dynamic systems analysis, created the scenario of land use planning in Ambon Bay Area that integrates land and wet land. The scenario used in this study is the optimistic, pessimistic and moderate scenarios. The variable that is used to determine of policy scenarios spatial planning based on the rate of population growth is 2,5% per annum, while variable forest area of at least 30% of the area. Of the three scenarios, the scenario chosen for the land use planning policy in Ambon Bay Areas in the future is to use the moderate scenario. The simulation results moderate scenario, the status of coastal ecosystems is improved from the criteria of the coastal ecosystem damaged by coastal ecosystems index 44,44% in 2008 turned into good condition with the index of coastal ecosystems 88,89% in 2029